Osmotically Driven Membrane Processes - Ince, Muharrem; Kaplan Ince, Olcay (IntechOpen, 2022)
Osmotically Driven Membrane Processes provides an overview of membrane systems and separation processes, recent trends in membranes and membrane processes, and advancements in osmotically driven membrane systems. It focuses on recent advances in monitoring and controlling wastewater using membrane technologies. It explains and clarifies important research studies as well as discusses advancements in the field of organic-inorganic pollution.